High-performance nanofibrous membrane for removal of Cr(VI) from contaminated water. (October 2015) - Liu, Yang; Ma, Hongyang; Liu, Brendan; Hsiao, Benjamin S; Chu, Benjamin
A simple and effective approach for the preparation of electrospun nanofibrous microfiltration membrane having positive surface charges, capable of removing Cr(VI) from contaminated water, was demonstrated. In this membrane, polyacrylonitrile was electrospun into a nanofibrous scaffold with an average fiber diameter of about 200 nm. Polyvinylamine, a positively charged polymer was grafted onto the nanofibrous scaffold through cross-linking reaction by glutaraldehyde. The microfiltration characteristics of the original and modified membranes, such as the maximum and mean pore size, particle rejection ratio, pure water flux and mechanical strength, were investigated. The effects of the pH value (1.0 to 13.0) and initial Cr(VI) concentration (5 mg/L to 100 mg/L) on the static adsorption rate of the membrane were also studied. Both experimental and theoretical results showed that the optimal pH range for Cr(VI) adsorption was from 3.0 to 5.0. Due to the high surface charge density, the polyvinylamine -grafted nanofibrous membrane exhibited a saturation adsorption capacity of 57.1 mg Cr(VI) per gram of the membrane, based on the Langmuir model analysis, and also a high Cr(VI) adsorption capacity in the dynamic adsorption test. In addition, this membrane could be regenerated from the desorption of Cr(VI) using a 0.1 mol/L of NaOH aqueous solution.